Contribution to the knowledge of the Mallophaga (Phthiraptera, Amblycera, Ischnocera) of the birds from Peru. Part 2 - Gomez-Puerta, Luis A. (2018)
This study presents twelve species of Mallophaga collected from birds held in captive in a temporary or permanent enclosure in Peru. Four Mallophaga Amblycera: Colpocephalum turbinatum, Psittacobrosus amazonicus, Psittacobrosus burmeisteri y Kurodaia sp., as well as eight Mallophaga Ischnocera: Neopsittaconirmus gracilis, Paragoniocotes fulvofasciatus, Paragoniocotes mirabilis, Paragoniocotes nanus, Paragoniocotes neivai, Paragoniocotes pyrrhurae, Philoceanus amadoni y Quadraceps burhinoides, were identified morphologically. A brief description of each chewing lice and discussion about their hosts and distribution were done.